Keterkaitan Stakeholders Melalui Beberapa Faktor terhadap Pengungkapan Emisi Karbo - Evelyn Nova Linda; Shanti Shanti (Organum: Jurnal Saintifik Manajemen dan Akuntansi, 2022)
In a business competition, company play a role in climate change which involved carbon emission. This has leads to emergence carbon emission disclosure caused by various factors. In this case, this study has a purpose to determine the relation of stakeholders through several factors on carbon emission disclosure. The research design used in this research is quantitative. The type of data used are secondary data, namely annual reports, sustainability reports, and PROPER ratings. All data used are secondary data. The research objects are all manufacturing, mining and plantation companies listed on the Indonesia Stock Exchange (IDX) in 2017—2019. The data analysis technique used is multiple linear regression analysis. The results showed that a green strategy had a positive effect on the carbon emission disclosure. The environmental management system has a negative effect on carbon emission disclosure. Environmental performance does not affect the carbon emissions. Carbon emission disclosure can be important when the company has carried out influencing criteria, so that some aspect references will help the company to whether or not to make disclosures.